Zabór palace in the light of the latest discoveries - interior of the elevation using sgraffito technology = Pałac w Zaborze w świetle najnowszych odkryć - dekoracja elewacji w technice sgraffita - Bielenis-Kopeć, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The property in Zabór from the fifteenth century belonged, among others, to families: von Tschammer, von Dyhrn, Montani, von Dünnewald, von Cosel and von Schönaich-Carolath. The testimony of its magnificence is a palace built by Count Johann Heinrich von Dünnewald in the 4th quarter of the seventeenth century, in the type of early baroque French residence, which, after 1745 was expanded in a magnificent baroque residence by Count Friedrich August von Cosel.
Keywords: Zabór; aroque residence; decoration on the facade; sgraffito; pałac barokowy; dekoracja elewacji